Novel in-situ constructing approach for vertically aligned AlN skeleton and its thermal conductivity enhancement effect on epoxy. Issue 4 (15th February 2023) - Wu, Liangqing; Xiang, Daoping
Abstract: As one of the key components of electronic devices, thermal management materials (TMMs) with high thermal conductivity are essential to ensure their safety and long service life. For polymer-based TMMs, AlN is one of the preferred fillers, but it has some drawbacks such as high cost and easy hydrolysis. Herein, a controllable and continuously oriented three-dimensional AlN skeleton (3D-AlNNS) was in-situ transformed from a low-cost 3D Al-containing skeleton (3D-AlNS) by combining the ice-templating and nitriding reaction sintering. Subsequently, AlN/epoxy composites were obtained by a vacuum infiltration. The composite containing 39.69 vol% AlN had the highest thermal conductivity of 4.29 W m −1 ·K −1, which was 21.45 times higher than that of pure epoxy. The composite substrates showed excellent heat dissipation performance in practical applications due to their high thermal conductivity. The continuous directional alignment of AlN powders in the 3D skeleton and intersection of AlN whiskers between the skeleton walls produced in-situ contributed to the formation of effective multichannel heat transferring paths and improvement in thermal conductivity. This novel approach has the advantages of low-cost, short processing time, simple operation and repeatability, and provides a new idea for developing heat-conducting polymer composites, which can also be extended to the preparation of similar TMMs.